Development of facilitated transport membranes with low viscosity aprotic heterocyclic anion type ionic liquid as a CO2 carrier. Issue 2 (22nd January 2017) - Kamio, Eiji; Matsuki, Tatsuya; Moghadam, Farhad; Matsuyama, Hideto
ABSTRACT: Low viscosity ionic liquids (ILs) composed of a cation with methoxy group and an aprotic heterocyclic anion (AHA) with highly nucleophilic amino group were synthesized and examined as a CO2 carrier of facilitated transport membranes. Due to the low viscosity of the AHA-type ILs after CO2 absorption, the AHA-type IL-based membrane showed high CO2 permeability ( ca . 3900 barrer) with 200 of CO2 /CH4 selectivity under dry condition at 323 K, which was much higher than that of amino acid ILs-based membrane ( ca . 150 barrer with ca . 50 of CO2 /CH4 selectivity).